2016
DOI: 10.1002/ab.21690
|View full text |Cite
|
Sign up to set email alerts
|

The effects of environmental resource and security on aggressive behavior

Abstract: Exposure to different environments has been reported to change aggressive behavior, but previous research did not consider the underlying elements that caused such an effect. Based on previous work on environmental perception, we examined the role of environmental resource and security in altering aggression level. In three experiments, participants were exposed to environments that varied in resource (High vs. Low) and security (High vs. Low) levels, after which aggression was measured. The environments were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…People expressed less aggression in resourcerich environments that felt safe, such as a savannah-like landscapes, but more aggression in environments with fewer resources and security, such as a desert. The authors suggested that the impact had more to do with resource availability, but the level of security played a role in the behavior and should not be overlooked [54]. Another study showed that children displayed more generous behaviors after being surrounded by tall trees [53].…”
Section: Pro-social Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation
“…People expressed less aggression in resourcerich environments that felt safe, such as a savannah-like landscapes, but more aggression in environments with fewer resources and security, such as a desert. The authors suggested that the impact had more to do with resource availability, but the level of security played a role in the behavior and should not be overlooked [54]. Another study showed that children displayed more generous behaviors after being surrounded by tall trees [53].…”
Section: Pro-social Behaviorsmentioning
confidence: 99%
“…More research is needed to establish stronger links between GI and pro-social behaviors, and many questions remain unanswered. For instance, all three of the Guégen et al [52], Piff et al [53], and Ng and Chow [54] studies reported different behaviors from two groups of participants. That means that we still did not know whether a person's tendency to exhibit pro-social behaviors can be influenced by GI exposure.…”
Section: Pro-social Behaviorsmentioning
confidence: 99%
“…Demanding climates in China, which threatened resource supply and safety, predicted higher social connectedness (Van de Vliert, Yang, Wang, & Ren, 2012). Exposure to high-resource-high-security natural environments led to lower aggression than those that were resource-poor or insecure (Ng & Chow, 2017). In urban settings, more helping was reported among people possessing more social and economic resources (Korndörfer, Egloff, & Schmukle, 2015) and in safe cities with lower crime rates (Bach, Defever, Chopik, & Konrath, 2017; Levine, Martinez, Brase, & Sorenson, 1994).…”
mentioning
confidence: 99%
“…The results supported our hypothesis. First, we found that the environment matters (Ng & Chow, 2017). Muslims living in vulnerable environments, perceived more conflict between them and Christians, reported having worse social integration, attended the mosque more frequently, and presented higher support for terrorist activities.…”
Section: Discussionmentioning
confidence: 86%